2017
DOI: 10.1038/s41598-017-00344-z
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation and calcium control syntaxin-1A and secretagogin sequestration by tomosyn to regulate insulin exocytosis in human ß cells

Abstract: Insulin secretion from pancreatic ß cells is a multistep process that requires the coordination of exocytotic proteins that integrate diverse signals. These include signals derived from metabolic control of post-translational SUMOylation and depolarization-induced rises in intracellular Ca2+. Here we show that tomosyn, which suppresses insulin exocytosis by binding syntaxin1A, does so in a manner which requires its SUMOylation. Glucose-dependent de-SUMOylation of tomosyn1 at K298 releases syntaxin1A and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…In fact, these ‘metabolic amplification’ pathways may act early to set the amplitude of glucose‐induced secretory responses – and reduced efficacy of this pathway may contribute to impaired insulin secretion in type 2 diabetes (T2D) (Grespan et al, 2018). One important pathway that contributes to the metabolic amplification of insulin secretion links the mitochondrial export of (iso)citrate and cytosolic generation of NADPH (Joseph et al, 2006; Ronnebaum et al, 2006) which facilitates insulin exocytosis (Ivarsson et al, 2005; Reinbothe et al, 2009) via the deSUMOylating enzyme sentrin‐specific protease‐1 (SENP1) (Ferdaoussi et al, 2015) acting on proteins at the exocytotic site (Dai et al, 2011; Ferdaoussi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these ‘metabolic amplification’ pathways may act early to set the amplitude of glucose‐induced secretory responses – and reduced efficacy of this pathway may contribute to impaired insulin secretion in type 2 diabetes (T2D) (Grespan et al, 2018). One important pathway that contributes to the metabolic amplification of insulin secretion links the mitochondrial export of (iso)citrate and cytosolic generation of NADPH (Joseph et al, 2006; Ronnebaum et al, 2006) which facilitates insulin exocytosis (Ivarsson et al, 2005; Reinbothe et al, 2009) via the deSUMOylating enzyme sentrin‐specific protease‐1 (SENP1) (Ferdaoussi et al, 2015) acting on proteins at the exocytotic site (Dai et al, 2011; Ferdaoussi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…My group and others have also shown that SUMOylation regulates exocytotic membrane fusion [14,23], and this appears to be mediated by direct SUMOylation of exocytotic proteins and consequent regulation of protein-protein interactions amongst members of the secretory machinery [21]. Intriguingly, SUMOylation is suggested to both increase and decrease exocytosis (for a review, see [24]).…”
Section: Downstream Sumo-dependent Mechanisms In Isletsmentioning
confidence: 99%
“…We know, for example, that increasing SUMOylation blunts glucose-stimulated insulin secretion by directly inhibiting insulin exocytosis [14,21], and that islet Senp1 knockout results in glucose intolerance without affecting islet mass or insulin content [18]. Conversely, upregulating Senp1 causes impaired insulin secretion while inducing beta cell apoptosis and sensitising to IL-1β-induced islet dysfunction and death [19].…”
Section: Sumoylation and The Isletmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, we noticed Secretagogin (SCGN; a six-EF hand Ca 2+ -binding protein) as an intriguing prospect. This is based on the facts that in pancreatic β-cells, SCGN regulates both the insulin expression (6) and the release (6)(7)(8)(9)(10). Moreover, SCGN seems to be synchronously secreted with insulin upon cAMP stimulation (11).…”
Section: Introductionmentioning
confidence: 99%